Pengembangan Modul Ajar Berbasis Karakter Untuk Program Anak Indonesia Hebat di TK Zainul Hasan - Fitriani, Rohyana; Adawiyah, Rabihatun; Ismi, Lailatul (Jurnal Ilmiah Global Education, 2025)
This research aims to develop character-based teaching modules to support the Great Indonesian Children Program at Zainul Hasan Masbagik Kindergarten. The program is designed to instil key character values such as responsibility, honesty, caring, discipline, and cooperation from an early age through a fun, contextual, and meaningful learning approach. The type of research used is Research and Development (R&D) by adapting the Borg & Gall development model, which consists of ten main steps: initial research and information gathering, planning, product draft development, initial field trial, initial product revision, main field trial, advanced product revision, operational trial, final product revision, and dissemination. The subjects in this study include teachers and group B students at Zainul Hasan Masbagik Kindergarten. Data collection techniques are carried out through observation, questionnaires, interviews, and expert validation. The data obtained was analysed qualitatively and quantitatively to determine the feasibility and effectiveness of the product. The data from the validation calculation by media experts show that the parenting module developed by the researcher can be categorized as "excellent". Meanwhile, the results of the study on the character of children aged 5-6 years after parents used the great Indonesian children's character-based teaching module implemented in schools showed a significant increase. The results of this research are expected to be able to produce teaching modules that are valid in content and structure, practical in application by teachers, and effective in improving early childhood character behaviour. This module is also expected to be replicated and adapted in other PAUD units as part of strengthening character education in Indonesia.